2013
DOI: 10.1002/hed.23357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pretreatment ideal body weight percentile and albumin on prognosis of nasopharyngeal carcinoma: Long-term outcomes of 512 patients from a single institution

Abstract: Decrease of pretreatment IBW% and albumin was related to poorer survival of NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 44 publications
2
50
1
1
Order By: Relevance
“…42 Although PEG catheterization is more receptive than nasogastric tubes, studies [43][44][45] have also shown that PEG may result in a decrease in swallowing process. 50 In addition, we observed that overweight patients receiving HEN still had decreased HB at week 2 and leukocytopenia at week 4 of CCRT. 46 However, whether PEG could cause swallowing disorders remains controversial.…”
Section: Discussionmentioning
confidence: 65%
“…42 Although PEG catheterization is more receptive than nasogastric tubes, studies [43][44][45] have also shown that PEG may result in a decrease in swallowing process. 50 In addition, we observed that overweight patients receiving HEN still had decreased HB at week 2 and leukocytopenia at week 4 of CCRT. 46 However, whether PEG could cause swallowing disorders remains controversial.…”
Section: Discussionmentioning
confidence: 65%
“…Full texts of these 16 remaining studies were assessed according to the inclusion and exclusion criteria, and 6 articles failed to offer sufficient prognostic information. Finally, as shown in Figure , a total of 10 studies comprising 7339 cases were included in this meta‐analysis . Patients were from different cancer centres and were assessed at different time points and differed in metastatic or non‐metastatic NPC.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, as shown in Figure 1, a total of 10 studies comprising 7339 cases were included in this meta-analysis. 20,21,[25][26][27][28][29][30][31][32] Patients were from different cancer centres and were assessed at different time points and differed in metastatic or non-metastatic NPC.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Several clinical studies have shown that patients receiving nutritional intervention survive longer. [12,13] Poor nutritional practices, which can lead to under-nutrition, can contribute to the incidence and severity of treatment side effects and increase the risk of infection and mortality in cancer patients. [2] Advanced colorectal cancer patients, especially those with malnutrition, experience poor general health and cannot adapt to project implementation.…”
Section: Discussionmentioning
confidence: 99%